Impact of Let’s Read and Kipin School 4.0 on Fourth Grade Reading Interest - Chrisnaji Banindra Yudha; Wahyu Setiawan; Dyah Anungrat Herzamzam (PUSAKA: Journal of Educational Review, 2025)
This study aims to demonstrate the influence of the Let’s Read and Kipin School 4.0 applications on the reading interest of fourth-grade students at Insan Madani Integrated Islamic Elementary School during the second semester of the 2023/2024 academic year. This research is quantitative with a quasi-experimental design, utilizing a pretest posttest control group design. There are three groups: experiment group 1 (Let’s Read), experiment group 2 (Kipin School 4.0), and a control group (using only reading books). The sample was taken through simple random sampling, and the instrument used was a questionnaire. Data analysis was conducted using t-tests after performing normality and homogeneity tests. The results show that H0 is rejected and Ha is accepted, indicating a significant influence of the applications on reading interest. The average posttest score for experiment group 1 is 74.30, for experiment group 2 is 70.67, and for the control group is 61.24. With a Sig (2-tailed) value of 0.000 < 0.05, there is a significant difference between the average scores of the experimental and control groups. The conclusion of this study indicates a positive effect of the Let’s Read and Kipin School 4.0 applications on students' reading interest compared to traditional methods.